Feminist Periodicals v.19, no. 4 (Winter 2000) - (:unkn) unknown (University of Wisconsin System Women's Studies Librarian's Office, 2000)
Sub-title: A Current Listing of Contents. 164p.
Table of contents periodical
Keywords: Women's Studies; Periodicals; Tables of Contents; Resources; Gender; Feminism; Lesbian Periodicals--Index; Women's Periodicals--Index